STUDY ANALYSIS OF ISTINBA METHOD 'NAHḌATUL' ULAMA’ (NU) IN MARRIAGE A DIFFERENT RELIGION - Abdul Hadi; Nurul Azizah; Nikmatus Sholihah (Pascasarjana Universitas Wahid hasyim Semarang, 2019)
Baḥṡul Masa'il Nahdlatul Ulama (BMNU) is the highest forum of NU which is responsible for making decisions relating to the term 'fiqhiyyah. Even problems of daily life that are not related to fiqh, such as the problem of monotheism, Sufism, tarekat, tradition, culture, and including issues of interfaith marriage can be resolved in this forum. Nowadays in Indonesia interfaith marriage is a familiar phenomenon among celebrities, ordinary people, even activists of interfaith dialogue and educated religious leaders. The law of interfaith marriage is a complicated and controversial issue among fuqaha '. The pros and cons of interfaith marriage are accompanied by the arguments of each party, starting from psychological, legal, and the most coloring are the issue of belief in religious interpretations. From the basis of taking the law used by the Bahtsul Masa'il Lajnah is the opinion of the statement of al-Sarqawi in his book Ḥasyiyah al-Sarqawi ‘ala Tufah. There, it has been very clearly explained with various reasons and legal considerations regarding interfaith marriages, therefore the Lajnah Ba'ul masaʻil can draw conclusions that interfaith marriages in Indonesia are included in prohibited and illegitimate marriages. Key Word: interfaith marriages, Istinbaṭ Nahḍatul ʻulama’ (Nu)